Experiences and emotions accompanying first-year students of Master’s speech therapy studies: Problem-based Learning at the Jagiellonian University: Nauczanie problemowe na Uniwersytecie Jagiellońskim - Dębski, Robert; Matusiak, Feliks; Młyński, Rafał (Logopedia Silesiana, 2020)
Problem-based Learning (PBL) has had a significant impact on tertiary education programs around the world in recent years, including programs in speech-language pathology. In Poland, the change from traditional teaching forms, such as lectures and classes, to problem-based tutorials has been a noticeable trend. There is a scarcity of research devoted to PBL adaptations in Poland, including research on student reception of this approach to education. The present study describes the experiences and emotions accompanying a purposive sample of six participants, firstyear students of Master’s speech therapy studies at Jagiellonian University, at the time of enrolling in the PBL program, during their studies and when they consider their future work as speech therapists. The phenomenological analysis of in-depth interview data has made it possible to identify several lead and peripheral themes which can become the basis of actions aimed at improving student response to problem-based learning in speech pathology education.